Tuning the Visible-Nir Absorption of Azulenocyanine-Based Photosensitizers - Cardenas-Jiron, G; Zambrano-Angulo, M; Granados-Tavera, K (Springer Science and Business Media Deutschland GmbH, 2022)
A new photosensitizer 1-WS55 (dyad) based on two dyes with excellent properties, azulenocyanine (1) and WS55, is proposed at the density functional theory level (M06/def2-SVP). 1 is a dye having a broad NIR absorption (~ 1000 nm), and WS55 is a metal-free organic dye that presents a huge photoelectric conversion efficiency (PCE) of 9.5%. The dyad presents a panchromatic absorption along the UV–Vis-NIR region. It exhibits two intense Q bands (880, 926 nm) in the NIR region, one strong band (672 nm) in the visible region, and several bands in 300–600 nm. Charge transfer bands in the dyad from 1 to WS55 were found in the visible region, which favors the adsorption on an anatase TiO2 surface. The interaction energies dyad (dye)-TiO2 were calculated as a periodic system and corrected by the basis set superposition error. These show better adsorption for the dyad than fragments 1 and WS55. The electron injection calculated from the dye (dyad) to TiO2 suggests an efficient solar energy conversion because of ΔGinj > 0.2 eV. Additionally, calculations performed for the reorganization energy of electrons and holes indicate that the dyad presents the highest charge mobility. In summary, the dyad proposed 1-WS55 constitutes an excellent candidate to be used as a potential photosensitizer for the DSSCs. Graphical abstract: [Figure not available: see fulltext.]. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.